Teeth : the story of beauty, inequality, and the struggle for oral health in America - Otto, Mary (The New Press, 2017)
This book takes readers on a disturbing journey into America's silent epidemic of oral disease, exposing the hidden connections between tooth decay and stunted job prospects, low educational achievement, social mobility, and the troubling state of our public health. The book's subjects include the pioneering dentist who made Shirley Temple and Judy Garland's teeth sparkle on the silver screen and helped create the all-American image of "pearly whites"; Deamonte Driver, the young Maryland boy whose tragic death from an abscessed tooth sparked congressional hearings; and a marketing guru who offers advice to dentists on how to push new and expensive treatments and how to keep Medicaid patients at bay. In one of its most disturbing findings, the book reveals that toothaches are not an occasional inconvenience, but rather a chronic reality for millions of people - including disproportionate numbers of the elderly and people of color. Many people, the author reveals, have a shrinking number of tangible options and resort to prayer to counteract the uniquely devastating effects of dental pain. The author also goes back in time to understand the roots of our predicament in the history of dentistry, showing how it became separated from mainstream medicine, despite a century of growing evidence that oral health and general bodily health are closely related. This book sparks an urgent conversation about why our oral health and our teeth matter. -- Adapted from publisher's description.
Keywords: Dental care.; Dental care, Cost of.; Dental hygiene.; Dental economics.; Medical policy.; Poverty.; Dental Care -- economics; Healthcare Disparities; Tooth Diseases -- complications; Dental Care -- history; Poverty; Health Policy; United States; Dental Care; Economics, Dental; Soins dentaires.; Soins dentaires -- Coût.; Hygiène dentaire.; Dentisterie -- Aspect économique.; Politique sanitaire.; Pauvreté.; poverty.; MEDICAL / Surgery / General; Medical policy; Dental care; Dental care, Cost of; Dental economics; Dental hygiene; POLITICAL SCIENCE / Public Policy / Social Services & Welfare